Pola strategi dan maksim kesantunan dalam rancangan bual bicara / Arina Johari - Arina , Johari (2019)
This study is conducted in order to explore and identify the politeness strategies in a talk show entitled “Celik Mata Reset Minda Orang yang Tenang” a programme aired by IKIMfm. The analysis of the data includes 28 context of conversations in 10 substructures involving 731 dialogues between the host, guest, callers and messages from the listeners. The dialogues were then analysed according to three different phases within the discussions (introduction, content and conclusion). The research seeks to complement the minimal amount of academic resources where talk shows corpus in Bahasa Melayu are concerned. Three main objectives were presented; to identify the structure and patterns of politeness, to analyse the use of combined strategies and the maxims. Last but not least, to relate the combined strategies and the maxims with the Malay form of politeness. The study evolved around two different theories; Brown and Levinson’s Politeness Theory (1987) and Grice’s Maxims (1975). These theories are then put together to create a model called “Model Pola Kombinasi Strategi dan Maksim (MPKSM)”. MPKSM forms four patterns of combined strategies that contain P1, P2 and P3 as the core patterns and optional patterns, namely Pattern A, Pattern B, Pattern C and Pattern D. Both patterns are then matched to the maxims of Cooperative Principles. P1 represents the Off Record sans match which was seen as optional, whereas P2 (a Politeness strategy, both positive and negative) was observed to be used as a core pattern. P3 (Off Record strategy) is used as an option in phrases that involved a certain combination that can be deemed as a core pattern. The findings have shown that the participants have applied a combined pattern as an opted strategy and maxim to minimize Face Threatening Act. The P2 combination is chosen when uttering responses during the talk show to ensure solidarity. Other emerging findings vi include the use of the 6 patterns in MPKSM - Pattern A first variation, Pattern A second variation, Pattern B first variation, Pattern B second variation, Pattern C first variation and Pattern C second variation. Pattern A second variation was used by all participants of the talk show and has shown the highest frequency of 513 dialogues (70.2%). Pattern B first variation was only used by the guest of the talk show with the lowest frequency of 12 dialogues (1.6%). Factors that may influence the participants’ politeness strategy; the concept of the talk show, the participants roles, observation of power and the presence of the public, are seen to be significant in determining their choice. Another interesting observation made through this study is that the Politeness Strategy of the participants is very much related to the Ciri Kesantunan Melayu (The Features of Malay Politeness) or CKM which comprises of (i) role + power + social status, (ii) adherence to the topic of the show and field of interaction, and (iii) adherence to the rules of interation. The participants are more inclined to observe Politeness when adhering to the rules of the show throughout the interaction. Hence, it can be deduced that the combination of the two theories of the West used in this study; B&L (1987) and Grice (1975); also CKM by three experts of Malay politeness, namely Asmah (2000), Tenas (2011) and Awang (2015) have been proven to reflect a comprehensive justification in the choice of politeness strategy used by the participants in the talk show “Celik Mata Reset Minda Orang Yang Tenang” aired by IKIMfm.